Opto-electronic analysis of Cs2PdCl2Br4 Perovskites compounds for photovoltaic applications - Soni, Amit; Sahariya, Jagrati; Bhamu, K. C.; Ahuja, Ushma (2018 International Conference and Utility Exhibition on Green Energy for Sustainable Development (ICUE), 2018)
In this paper, electronic and optical properties of Cs2PdCl2Br4 perovskite compound are presented using full potential linearized augmented plane wave (FP-LAPW) method. All computations are performed using most accurate modified Becke Johnson (mBJ) potential within density functional theory. Energy band computations are performed over here to elaborate relationship between energy and wave vector (k). Pattern of occurrence observed for energy bands are analyzed in terms of plotted total and partial density of states. For investigating optical behavior of Cs2PdCl2Br4, we have computed dielectric tensor, absorption spectra, reflectivity and refraction spectra using mBJ potential. Different peaks recorded in the imaginary components of dielectric tensor are interpreted in terms of interband transitions for better understanding. Significant absorption intensity available in desired energy range and suitable band gap indicates effective utilization of this compound in photovoltaic applications.

Opto-electronic analysis of promising photovoltaic Cs2PdCl4Br2: An upcoming perovskite material - Sahariya, J.; Soni, A.; Bhamu, K. C. (WIECON-ECE 2017 - IEEE International WIE Conference on Electrical and Computer Engineering 2017, 2018)
he metal halide perovskites are attracting much attention due to their potential applications in optoelectronic devices. Herein, we review and calculate a new avenue for Cs 2 PdCl 4 Br 2 perovskites by computing its electronic and optical properties to show its candidature in optoelectronics. For the computation of electronic and optical properties, we have used modified Becke Johnson approximation available in Wien2k code, based on full potential linearised augmented plane wave method. Investigated electronic and optical properties show that Cs 2 PdCl 4 Br 2 has the indirect band gap of 1.70 eV. The significant intense peaks in absorption spectra between energy range 2-3 eV reveals the utility of this compound in solar cells and other optoelectronic devices.